2019
DOI: 10.1029/2018jb016722
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Pressure Curve Determination Based on a 2‐D Cross‐Section Analysis Via Fractal Geometry: A Bridge Between 2‐D and 3‐D Pore Structure of Porous Media

Abstract: Pore structure is a crucial attribute in characterizing fluid flow through porous media. However, direct experimental measurements or numerical reconstructions are commonly expensive and not environmentally friendly, with great uncertainty caused by the complex nature of porous media. In this study, we demonstrate that one special bridge function, which is a function of the apparent length and tortuosity fractal dimension, can characterize the relationship of pore structures between two dimensions (2‐D) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 68 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…The classical Watershed (WS) algorithm is widely used to segment two connected pore bodies in porous media (Chen et al., 2019; Rabbani et al., 2014). However, whether WS algorithm can segment fracture surface remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical Watershed (WS) algorithm is widely used to segment two connected pore bodies in porous media (Chen et al., 2019; Rabbani et al., 2014). However, whether WS algorithm can segment fracture surface remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…TS visualizes these invisible pores and microfractures on the mesoscopic scale between macroscopic identification and microscopic SEM. TS was successfully applied in sandstone reservoirs to analyze 2D pore structure and associated diagenesis (the dissolution, compaction of grain and the evolution of clay minerals) (Chen & Yao, 2017; Chen et al., 2019). In this work, microfractures morphologies of coal samples including intact coal (Nos.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…If the reference cross section is used as the research object, the relationship between the effective porosity ϕ and the reference porosity ϕ r can be expressed as ϕ = ϕ r c , where c is defined as the nonuniformity factor. However, in practice, the reference porosity is not necessarily greater than the effective porosity [37], so the range of the nonuniformity factor c should be c > 0, more specifically, when the reference porosity is greater than the effective porosity, c > 1; when the reference porosity is less than the effective porosity, 0 < c < 1; and when the reference porosity equals to the effective porosity, c = 1.…”
Section: The Permeability Of Nonuniform Cross-sectional Poresmentioning
confidence: 99%
“…In the model, the Sierpinski fractal was utilized to construct the geometry structure of porous media. In the study of Chen et al [34], they demonstrated that one special bridge function, which was a function of the apparent length and tortuosity fractal dimension, could characterize the relationship of pore structures between two dimensions (2-D) and three dimensions (3-D), and it could serve as a conversion bridge of the radius to determine the capillary pressure curve. In view of the evolution characteristics of micropore-throat structure of longterm waterflood reservoir, most scholars described it through laboratory experiments and field coring data, but few scholars proposed to apply fractal theory to it to realize the quantitative characteristics of its change law in theory.…”
Section: Introductionmentioning
confidence: 99%